A critique of Confucius' philosophy. Issue 4 (1st October 2016) - Yang, Michael Vincent
ABSTRACT: Throughout the millennia since the composition of the Analects, orthodox scholars have maintained that Confucius faithfully passed down the thought of early eras, particularly those of Yao and Shun: 'I transmit but do not create ideas.' This paper shows that Confucius actually subverted the essence of orthodox thought represented mainly by Yao and Shun. His subversion of orthodox thought compels perforce the idea of 'ren (humanity), ' which concerns itself with the human world, to stand out with the near exclusion of otherworldliness in his teaching. As a result of the misunderstanding of Confucius' heritage, scholars in the past tended to equate Confucius' idea of 'ren' with specific moral attributes. Again taking exception to the interpretations of bygone eras, this essay demonstrates that humanity in Confucius' theory signifies a dynamic process rather than a specific attribute or a static rule, changing constantly with different people, different places, and different times.